(untitled) (Texas Journal of Engineering and Technology, 2022)
The article discusses ways to improve the operational properties of hydraulic oils for agricultural machinery. The results of laboratory studies of hydraulic oils with an additive based on zinc dithiophosphate ZD-40 and recommendations for their use are presented. During agricultural work, tractor engines due to congestion and oxidation of carbon, the content of carbine, carbide and asphalt products increases by 1.2%. In addition, analytical relationships were obtained representing the movement of a mixture of acetone and used motor oil in viscosity states and the process of evaporation of the solvent from the oil during processing. The speed of motor oil on a cone-shaped surface is substantiated based on its effect on refining, and the dependence of the quality of refined oil on the temperature of the mixture and the availability of the evaporation process is justified.